THE INFLUENCE OF PRODUCT COMPLETENESS, OUTLET ATMOSPHERE, SERVICE QUALITY, AND PRICE PERCEPTION ON PURCHASING DECISIONS AT KIMIA FARMA PHARMACY, SAM RATULANGI MANADO - Maulana, Gilang Rizki; Tumbuan, Willem JF Alfa; Soepeno, Djurwati (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to analyze the effect of product completeness, outlet atmosphere, service quality, and price perception on purchasing decisions at Kimia Farma Sam Ratulangi Manado Pharmacy, both simultaneously and partially. This study uses a descriptive approach with a quantitative method, without comparing or connecting independent variables with other variables. Data were collected through questionnaires distributed to consumers who visited the pharmacy during the last six months, with a total population of 48,359 people. Sampling was carried out randomly, with a minimum of 30 samples and a maximum of 500 samples. The number of samples in this study was 248 people. The analysis methods used were validity, reliability, classical assumptions, hypothesis testing and multiple linear regression analysis using the SPSS version 27 application. Based on the test results, it can be concluded that product completeness, outlet atmosphere, service quality, and price perception simultaneously and partially have a positive and significant effect on purchasing decisions at Kimia Farma Sam Ratulangi Manado Pharmacy.